Features of the unarmed resistance in Vilnius during the Soviet era - Klumbys, Valdemaras (Genocidas ir rezistencija, 2025)
This article analyses the features of the unarmed resistance in Vilnius, explains what made it stand out in the context of Lithuania as a whole, and looks for the causes and consequences of these differences. The focus is on the 1950s and 1970s, when resistance activities were the most visible. The assumption is made that the “capital climate” – the specific state policy in the capital city – encouraged residents to be more adaptable and look for more moderate ways to achieve their goals. The heightened influence of the ideas of Russian dissident on the resistance in Vilnius is evident; this also affected the methods of resistance, with open dissent standing out in Lithuanian underground activities in Vilnius. Also important in the Vilnius resistance were groups with little connection to religious resistance networks.